1983
DOI: 10.1002/jcp.1041170113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA) on the growth inhibitory and increased phosphatidylinositol (PI) responses induced by epidermal growth factor (EGF) in A431 cells

Abstract: Epidermal growth factor (EGF) inhibited the growth of A431 human epidermoid carcinoma cells. The tumor promoting, phorbol ester, 12-O-tetradecanoylphorbol-13-acetate (TPA) also retarded A431 cell growth. Addition of both TPA and EGF inhibited cell growth in an additive or synergistic manner depending upon the initial plating density of the cultures. EGF increased the production of diacylglycerol (60-70%) and stimulated the synthesis of phosphatidylinositol (PI) from 3H-inositol (three- to fourfold increase). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
21
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 42 publications
8
21
0
Order By: Relevance
“…However, the inhibitory effect of TPA on A431 cell growth was rather weak. The result is compatible with the pre vious report that demonstrated, a weak inhibi tion of A431 cell growth by TPA (8). It has generally been accepted that ODC induction is closely related to cell proliferation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the inhibitory effect of TPA on A431 cell growth was rather weak. The result is compatible with the pre vious report that demonstrated, a weak inhibi tion of A431 cell growth by TPA (8). It has generally been accepted that ODC induction is closely related to cell proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that protein kinase C plays an essential role in TPA-evoked ODC induction in mouse skin and epidermal cells (5 -7) , targets of skin tumor promotion by this agent. It has been reported that TPA inhibits the growth of A431 human epidermoid carci noma cells (8). To examine the role of protein kinase C in ODC induction in the cells whose growth is inhibited by TPA, we examined the effects of TPA and protein kinase C activators on serum factor(s)-caused ODC induction in A431 cells and found that ODC induction is negatively regulated by the protein kinase C system in these cells.…”
mentioning
confidence: 99%
“…Effects of Specific Inhibitors of Signal Transducers on a a 1 -Adrenergic Agonist Phenylephrine-Induced ERK Isoform Phosphorylation in the Presence of EGF The effects of a 1 -adrerenergic agonists on induction of ERK1/2 phosphorylation by 20 ng/ml EGF were investigated using the a 1 -adrenergic agonist phenylephrine (10 Ϫ6 M 36) ) and 12-O-tetradecanoylphorbol-13-acetate (phorbol ester, TPA 37) ). When hepatocytes were stimulated with EGF in the presence of phenylephrine (10 Ϫ6 M), and/or TPA (10 Ϫ7 M), significant potentiation of ERK2 phosphorylation was not observed when compared with EGF (20 ng/ml) alone (Fig.…”
Section: Effect Of Specific Inhibitors Of Signal Transducers Onmentioning
confidence: 99%
“…Fetal calf serum may activate protein kinase C (Moolenaar et al 1981;1983) and so desensitization of receptors may occur which alters the contractile response. TPA may inhibit diacylglycerol formation by epidermal growth factor (Smith, Losonczy, Sahai, Pannerselvam, Fehnel & Salomon, 1983) and TPA may attenuate the stimulation of Na+-H+ exchange by epidermal growth factor (Whiteley, Cassel, Zhuang & Glaser, 1984). Capogrossi et at.…”
Section: K T Macleod and S E Hardingmentioning
confidence: 99%